Marine Forearc Extension in the Hikurangi Margin: New Insights From High‐Resolution 3‐D Seismic Data. Issue 5 (21st May 2018) - Böttner, Christoph; Gross, Felix; Geersen, Jacob; Crutchley, Gareth J.; Mountjoy, Joshu J.; Krastel, Sebastian
Abstract: Upper‐plate normal faults are a widespread structural element in erosive plate margins. Increasing coverage of marine geophysical data has proven that similar features also exist in accretionary margins where horizontal compression usually results in folding and thrust faulting. There is a general lack of understanding of the role and importance of normal faulting for the structural and tectonic evolution of accretionary margins. Here we use high‐resolution 2‐D and 3‐D seismic reflection data and derived seismic attributes to map and analyze upper‐plate normal faulting in the marine forearc of the accretionary Hikurangi margin, New Zealand. We document extension of the marine forearc over a wide area along the upper continental slope. The seismically imaged normal faults show low vertical displacements, high dip angles, a preference for landward dip, and often en echelon patterns. We evaluate different processes, which may cause the observed extension, including (1) stress change during the earthquake cycle, (2) regional or local uplift and decoupling of shallow strata from compression at depth, and (3) rotation of crustal blocks and resulting differential stresses at the block boundaries. The results suggest that normal faults play an important role in the structural and tectonic evolution of accretionary margins, including the northern Hikurangi forearc. Key Points: High‐resolution 3‐D seismic data indicate widespread normal faulting on the upper slope of the northeastern Hikurangi margin The normal faults show two major strike directions, primarily landward dip, low vertical displacements, and steep dip angles Extension may be controlled by regional uplift or/and extensional strain due to rotation of tectonic blocks around nearby poles